Relative Nonlinear Measure Method to Exponential Stability of Impulsive Delayed Differential Equations - Xueli Song; Xing Xin; Huiya Dai; Jigen Peng (Abstract and Applied Analysis)
This paper is devoted to providing a novel method to global exponential stability of impulsive delayed differential equations. By utilizing relative nonlinear measure method, several global exponential stability criteria are presented for the impulsive delayed differential equations. Compared with the Razumikhin technique and Lyapunov function method, our method is less conservative and gives a convergence rate, and one of our stability criteria is more flexible by incorporating an adjustable matrix. An example and its simulation are provided to illustrate that our method is efficient and our results are new and correct.